On the Untraceability of Anonymous RFID Authentication Protocol with Constant Key-Lookup - LIANG, Bing (Institutional Knowledge at Singapore Management University, 2009)
In ASIACCS'08, Burmester, Medeiros and Motta proposed an anonymous RFID authentication protocol (BMM protocol [2]) that preserves the security and privacy properties, and achieves better scalability compared with other contemporary approaches. We analyze BMM protocol and find that some of security properties (especial untraceability) are not fulfilled as originally claimed. We consider a subtle attack, in which an adversary can manipulate the messages transmitted between a tag and a reader for several continuous protocol runs, and can successfully trace the tag after these interactions. Our attack works under a weak adversary model, in which an adversary can eavesdrop, intercept and replay the protocol messages, while stronger assumptions such as physically compromising of the secret on a tag, are not necessary. Based on our attack, more advanced attacking strategy can be designed on cracking a whole RFID-enabled supply chain if BMM protocol is implemented. To counteract such flaw, we improve the BMM protocol so that it maintains all the security and efficiency properties as claimed in [2].